Achieving successful business outcomes : driving high performance & effective transformations in a continuously evolving business environment - Sinha, Alok K. (New York, NY : Routledge, Taylor & Francis Group, 2020)
'Navigating in space is exponentially more difficult than navigating on the road - because there are too many directions to investigate, too many unknowns to be prepared for and infinite pathways to chart in the galactic system. So, it is with business. Business environments are extremely demanding and change continuously, precipitated by an innumerable number of actors and conditions. Business success can no more be predicated on the pedigree of a leader or a prescribed theory alone and the startups have amply proven this. Large companies have tried to copy the nimble-footed startups while startups after achieving a certain size have been forced to adopt unchartered path. Disruptions seems to be the order of the day. Achieving Successful Business Outcomes is about achieving successful business outcomes. Just like an aircraft has a rich dashboard of dials but only a critical few need to be monitored continuously while other subsets warrant attention only during specific phases of the flight, a well modelled business can be managed successfully using a similar strategy. But the larger question is how to model a business, with closely correlated variables, that represents the reality of the environment and allows devising, formulating and adjusting business strategy and actions in real-time. The author uses a simple but well-researched STA-Triangle (Space, time and action) model to achieve this purpose. The core of the STA Model is to help navigate effectively in a rapidly changing business environment. Unlike traditional business studies that use a single lens to define business rules or organizational practices, it uses the combination of space, time and action as the driver of outcomes - something fundamental and core to human thinking across the ages. This book contains both theoretical and practical applications, the former that can help propel further research and analysis, while the latter can help practicing leaders to drive their firms forward, confidently, in any environmental conditions. It will also help casual readers to understand how the future is evolving and how different organizations are responding to this change. The author includes more than a hundred supporting case studies and tools that help create highly incisive and unique views for calibrating strategy and execution'--
Includes bibliographical references and index.
Keywords: Success in business; Organizational change